Numerical simulation of the fluid-solid coupling mechanism of water and mud inrush in a water-rich fault tunnel. (January 2023) - Xie, Qiang; Cao, Zhilin; Sun, Weichen; Fumagalli, Alessio; Fu, Xiang; Wu, Zhihui; Wu, Kai
Highlights: A new CFD-DEM model is developed by coupling ABAQUS and PFC3D. An engineering-scale CFD-DEM model is used to simulate water and mud inrush. The evolution process of water and mud inrush in a water-rich fault is analyzed. The negative pore pressure phenomenon is found in water and mud inrush. Abstract: This study developed a new model, a 3D coupled computational fluid dynamics (CFD)-discrete element method (DEM) model, by coupling two software programs, ABAQUS and PFC3D, to solve problems related to fluid-solid interaction systems. The complete governing equations and the two-way coupling process between the two software are presented herein. Via Transmission Control Protocol (TCP) socket communication with Python scripting, information between the two software is exchanged in real-time. Then, the classic example in the PFC5.0 documentation was used to verify the model. In the end, the ABAQUS-PFC3D model was employed to simulate the process of water and mud inrush in a water-rich fault tunnel, which could reflect the evolution process of water and mud inrush and track particle movement in a fault zone. The results show that the particles that collapsed inside the fault formed an ellipsoidal distribution during the water and mud inrush in a water-rich fault tunnel. With the continuous loss of particles in the fault into the tunnel, the migration of particles is discontinuous, and a large void appears inside the fault zone. The rapid change of the groundwater flow velocity caused the negative pore pressure. The pressure arch force structure is formed above the ellipsoidal collapse area inside the fault. The principal force field of the fault areas changes from close to the dip of the fault to close to the perpendicular to the fault.